Comparative Genome Analysis and Spore Heat Resistance Assay Reveal a New Component to Population Structure and Genome Epidemiology Within Clostridium perfringens Enterotoxin-Carrying Isolates - Jaakkola, Kaisa; Virtanen, Kira; Lahti, Päivi; Keto-Timonen, Riikka; Lindström, Miia; Korkeala, Hannu (Frontiers in Microbiology, 2021)
Clostridium perfringens causes a variety of human and animal enteric diseases including food poisoning, antibiotic-associated diarrhea, and necrotic enteritis. Yet, the reservoirs of enteropathogenic enterotoxin-producing strains remain unknown. We conducted a genomic comparison of 290 strains and a heat resistance phenotyping of 30 C. perfringens strains to elucidate the population structure and ecology of this pathogen. C. perfringens genomes shared a conserved genetic backbone with more than half of the genes of an average genome conserved in >95% of strains. The cpe-carrying isolates were found to share genetic context: the cpe-carrying plasmids had different distribution patterns within the genetic lineages and the estimated pangenome of cpe-carrying isolates had a larger core genome and a smaller accessory genome compared to that of 290 strains. We characterize cpe-negative strains related to chromosomal cpe-carrying strains elucidating the origin of these strains and disclose two distinct groups of chromosomal cpe-carrying strains with different virulence characteristics, spore heat resistance properties, and presumably, ecological niche. Finally, an antibiotic-associated diarrhea isolate carrying two copies of the enterotoxin cpe gene and the associated genetic lineage with the potential for the emergence of similar strains are outlined. With C. perfringens as an example, implications of input genome quality for pangenome analysis are discussed. Our study furthers the understanding of genome epidemiology and population structure of enteropathogenic C. perfringens and brings new insight into this important pathogen and its reservoirs.